Efficacy of Pharmacological Therapies for Adhesive Capsulitis of the Shoulder: A Systematic Review and Network Meta-analysis. Issue 14 (December 2019) - Kitridis, Dimitrios; Tsikopoulos, Konstantinos; Bisbinas, Ilias; Papaioannidou, Paraskevi; Givissis, Panagiotis
Background: Several pharmacological interventions are used for the management of adhesive capsulitis of the shoulder, although the optimal treatment has yet to be defined. Purpose: To conduct a network meta-analysis to compare the effects of different pharmacological interventions for adhesive capsulitis, administered either alone or after distension of the shoulder capsule. Study Design: Network meta-analysis. Methods: The authors searched Scopus, PubMed, and the Cochrane Central Register of Controlled Trials up to April 22, 2018, for completed studies. They enrolled trials that assessed the results of different pharmacological treatments for the primary management of adhesive capsulitis. The primary outcome was pain relief as measured by self-administered questionnaires. The secondary outcome included the assessment of composite instruments that evaluated, at a minimum, pain and function. The authors clinically interpreted the results after back-transforming the standardized mean differences into mean differences in simple instruments and assessed the quality of the source studies using the Cochrane "risk of bias" tool. Results: The authors considered 30 trials with a total of 2010 participants in this systematic review. For pain relief, there was a significant difference in favor of intra-articular corticosteroids and distension of the shoulder capsule with steroids as compared with control in the short term (mean difference in visual analog scale (VAS): –1.4 [95% CI, −2.5 to −0.4] and −1.7 [95% CI, −3.2 to −0.1], respectively). Furthermore, rotator-interval injections were found to be superior to placebo (mean difference in VAS: –7.2; 95% CI, −10.1 to −4.4), although the intervention was considered in only 1 trial. Finally, there was a statistically significant difference in favor of multiple-site corticosteroid injections compared to placebo in both the short- (mean difference in Shoulder Pain and Disability Index [SPADI]: −86.7; 95% CI, −133.6 to −40) and intermediate-term assessment (mean difference in SPADI: −102.9; 95% CI, −163.9 to −41.8). Conclusion: Intra-articular corticosteroid intervention, administered either alone or after distension of the shoulder capsule, provided clinically meaningful improvements in the short term. Likewise, rotator-interval corticosteroid injections yielded promising results in terms of pain relief. However, these short-term benefits of steroids dissipated over time. Multiple-site corticosteroid injections showed clinical advantage over placebo for short- and intermediate-term composite outcome assessments.